2022
DOI: 10.1111/eos.12868
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bonding agent application method on the dentin bond durability of a two‐step adhesive utilizing a universal‐adhesive‐derived primer

Abstract: This study investigated the effect of the bonding agent application method on the dentin bond durability of a two‐step adhesive utilizing a universal‐adhesive‐derived primer. The bonding durability of a universal adhesive was compared with those of two conventional two‐step adhesives by shear bond strength testing after thermal cycling. The primer was applied (with or without phosphoric acid pre‐etching), and the specimens were divided into three groups based on the bonding agent application method used as fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Kasahara et al demonstrated that the reaction layer was clearly observed when using universal adhesives in ER mode but was unclear underneath the hybrid layer in a threestep or a two-step ER system (Optibond FL, Scotchbond Multi-purpose Plus, and Adper Single Bond Plus) 29) . However, two-step SE adhesives in ER mode showed a clear reaction layer similar to those of universal adhesives in ER mode 30) . Hence, the reaction layer may be a Ca salt resulting from a chemical reaction between HAp in the dentin and functional monomers.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Kasahara et al demonstrated that the reaction layer was clearly observed when using universal adhesives in ER mode but was unclear underneath the hybrid layer in a threestep or a two-step ER system (Optibond FL, Scotchbond Multi-purpose Plus, and Adper Single Bond Plus) 29) . However, two-step SE adhesives in ER mode showed a clear reaction layer similar to those of universal adhesives in ER mode 30) . Hence, the reaction layer may be a Ca salt resulting from a chemical reaction between HAp in the dentin and functional monomers.…”
Section: Discussionmentioning
confidence: 83%
“…Hence, the reaction layer may be a Ca salt resulting from a chemical reaction between HAp in the dentin and functional monomers. In particular, MDP-containing adheive systems showed a clearer reaction layer than adhesive systems containing other functional monomers 15,[29][30][31] . Therefore, the strength of expression of this layer might be related to the tyeps of functional monomers employed and their ability to penetrate the hybrid layer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…7 With the intention to increase the durability by a separate hydrophobic resin application, a new twostep HEMA-free adhesive system comprising a universaladhesive-derived primer and a highly hydrophobic agent has been launched with promising in vitro results. [54][55][56] The purpose of developing two-step universal adhesives was to separate the priming and sealing steps of adhesive bonding agent to obtain a thicker adhesive-resin film thickness. 51 All the universal adhesives contain water in their composition.…”
Section: Some Clinical Advice For a Durable Bonding Performance With ...mentioning
confidence: 99%
“…A new type of two-step SE adhesive system comprising a HEMA-free primer and a hydrophobic bonding agent has been developed using universal adhesive technology [24][25][26] . Unlike the traditional primer in three-or two-step adhesive systems, this new type of adhesive primer's components are similar to those of universal adhesives, containing 4-methacryloxyethyl trimellitic acid (4-MET) and 10-methacryloyloxydecyl dihydrogen phosphate (MDP) as functional monomers, in addition to a dimethacrylate monomer, filler, and photoinitiator.…”
Section: Introductionmentioning
confidence: 99%